"Data-Driven Optimization of IoT Network Efficiency and Anomaly Detection Using Deep Neural Networks" (Journal of the College of Basic Education, 2024)
The Internet of Things (IoT) is growing rapidly and presents enormous opportunities—but also some substantial difficulties—mostly having to do with managing and securing network traffic. With billions of interconnected devices, producing unfathomable amounts of data every second, the IoT demands a new kind of network infrastructure, one capable of being both reliable and secure from outside threats. At present, much of the onus for these twin conditions of network performance and security falls on the IoT itself. Yet researchers at the Grady College of Journalism and Mass Communication at the University of Georgia have taken a step toward something closer to ideal by wiring up a comprehensive, multilayer neural network and feeding its various parts a stream of conditions typical for the network during its normal operation. An input layer corresponding to the characteristics of the IoT network traffic precedes several hidden layers in the architecture. These hidden layers are designed to discern complex and intricate patterns within the network traffic data. In order to mitigate overfitting that might occur if the model is too perfectly matched to the training data, a dropout technique was incorporated as part of the architecture. The output layer uses a softmax activation function to produce a multi-class discrimination result those signals whether the network traffic being analyzed is normal or anomalous. Overall, the structure of the model is such that advanced machine learning techniques can be leveraged in order to identify and respond to any IoT traffic anomalies that occur, thus improving the performance of the network in question.We carry out meticulous data preprocessing, purposeful model architecture design, and a comprehensive and layered evaluation that utilizes various performance metrics. In comparison with some of the most commonly used algorithms for anomaly detection, our approach clearly demonstrates superior accuracy and a more efficient data flow in the IoT network. Additionally, we detail how our model could be used in a real-time the application and how well it scales to operate in the large, high-traffic, and dynamic environments that characterize the modern IoT network